Reflective Thinking of Undergraduate Students in Microbiology Lab Experiments - Amelia, Trisna; Liliasari, ‎; Kusnadi, ‎; Aditiawati, Pingkan (KnE Social Sciences, 2024)
This study attempts to examine undergraduate students’ reflective thinking while conducting microbiology lab activities. A collection of particular questions designed to elicit reflective thinking abilities were used in the context of microbiology lab activities to conduct this research utilizing a quantitative descriptive methodology. 32 undergraduate students taking microbiology classes in their fourth semester at a public university in Bandung, Indonesia, served as the study’s subjects. The findings demonstrated that reflective thinking arose in microbiology lab studies at the cognitive presence stage’s resolution phase. Even so, just a small portion (6%) of all the introspective remarks that students have written, had the look of reflection. Students frequently consider the triggering event (49%) and exploration (32%), in that order. The conclusions of this study suggest that microbiological lab activities should be created in a way that promotes the growth of reflective thinking by giving students the chance to perform more challenging laboratory tasks in addition to completing experiments. Keywords: reflective thinking, microbiology, lab experiments